Erratum: Synthesis of most polyene natural product motifs using just 12 building blocks and one coupling reaction - Woerly, Eric M.; Roy, Jahnabi; Burke, Martin D. (Nature chemistry, 2014)
Nature Chemistry 6, 484–491 (2014); published online 11 May 2014; corrected after print 18 May 2014. In the version of this Article originally published, the Competing Financial Interest statement provided by the authors at submission was inadvertently removed during the production process. It should read “The University of Illinois has filed patents on MIDA boronate chemistry.